(3CQLhRI aj UMI GdCLSGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jbhd QGLi QHg GHf SjfG hde jRd HGddg eSJYjfG jG SGFdi Yf UMI GdCLSGO GSeY UMjM GdWH HGdESfGO s
(3BNQgG (B:s
(3eG OGe aUd GdHQO hGdNQja cPGi QHjY GdhQO hGdeUja hGdMeO ddg Ydi GdEfYGe hGdTcQ dGRe Ydi GdESdGe s
(3Vef eLehY s
(3GfXQgG eY CQLhRI ai GdWH dGHf SjfG (B_ (3fSNI BjI Gddg GdMcje GdYGeI (B" (3Qbe (B301"s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B14 s
Keywords: (3GdWHs